Minimal Intervention Dentistry: Biocompatibility and Mechanism of Action of Products for Chemical-Mechanical Removal of Carious Tissue - Roberta Duarte Leme; Giuliana de Campos Chaves Lamarque; Laura Alves Bastos; Maya Fernanda Manfrin Arnez; Francisco Wanderley Garcia Paula-Silva (Frontiers Media S.A., 2022)
Conventional method for removal of carious tissue using low speed drills usually induce noise and vibration, in addition to thermal and pressure effects that can be harmful to the pulp tissue and cause fear in children. Therefore, several alternative methods are being developed to try to minimize the unpleasant perception of the patient during caries removal. Chemical-mechanical removal of carious tissue goal is to selectively remove the carious lesion, which reduces the amount of bacteria inside the cavity without removing the tissue susceptible to remineralization. This method is also able to minimize the tactile perception by the patient during the manipulation of the lesion compared to the conventional method, and, therefore, it has been widely accepted among phobic patients, children and special needs patients. Due to the close relationship between dentin and pulp tissue, all injuries imposed on this dentin may have repercussions on the underlying pulp connective tissue. The morphological aspects of remaining dentin favor the diffusion of chemical components of dental materials, which can be toxic to the pulp tissue or even negatively interfere in the reparative process. Thus, considering the proximity between the applied material and the underlying pulp tissue, especially in deep cavities, there is a need to assess the biological behavior of dental materials against pulp cells, since aggressions to the pulp tissue can be caused not only by metabolites from microorganisms involved in dental caries but also by components that are released from these products. This subject was explored in this narrative literature review.